Fungsi Organizing dan Comanding dalam Manajemen Pendidikan - Khusni Mubarok; M Za’iim Al Hisyam; Aris Wahyu Aji (Qawa’id: Jurnal Bahasa dan Sastra Arab, 2026)
This study aims to analyze the implementation of the organizing and commanding functions in Islamic educational management and their influence on the effectiveness of educational institution management. The research employed a qualitative approach using the library research method by examining various scholarly sources, including books, journal articles, and relevant academic documents. The data were analyzed through content analysis to identify the concepts, patterns, and implementation of these two management functions within the context of Islamic education. The findings reveal that the organizing function plays a crucial role in task allocation, organizational structure development, human resource coordination, and the proportional distribution of authority and responsibilities. Meanwhile, the commanding function is reflected through communicative leadership, guidance, motivation, supervision, and decision-making oriented toward achieving institutional goals. The integrated implementation of these two functions significantly enhances the effectiveness of Islamic educational institution management, as evidenced by improved coordination among organizational units, increased discipline among educators and educational staff, greater efficiency in program implementation, and the establishment of a professional organizational culture based on Islamic values. Therefore, the systematic implementation of the organizing and commanding functions constitutes a strategic factor in realizing effective, adaptive, and sustainable governance of Islamic educational institutions amid the dynamic development of the educational sector.